Shifting the paradigm of type 1 diabetes: a narrative review of disease-modifying therapies - O’Donovan, Alexander J.; Gorelik, Seth; Nally, Laura M. (Frontiers in Endocrinology, 2024)
A new diagnosis of type 1 diabetes (T1D) may be accompanied by numerous lifelong financial, emotional, and physical challenges, thus advancements in therapies that can delay the onset of clinical disease are crucial. T1D is an autoimmune condition involving destruction of pancreatic beta cells leading to insulin deficiency, hyperglycemia and long-term insulin dependence. The pathogenesis of T1D is classified into stages, with the first signal being the detection of autoantibodies without any glycemic changes. In the second stage, dysglycemia develops without symptoms, and in stage 3, symptoms of hyperglycemia become apparent, and at this time a clinical diagnosis of T1D is made. As a greater understanding of these stages of T1D have evolved, research efforts have been devoted to delaying the onset of clinical disease. To date, only one medication, teplizumab, has been approved by the Food and Drug Administration (FDA) for the treatment of stage 2 T1D. This narrative review present published trials and ongoing research on disease modifying therapies (DMT) in T1D, the mechanisms of action for each therapy, and the stages of T1D that these interventions are being studied.